STRATEGI BRANDING DIGITAL LEMBAGA PENDIDIKAN ISLAM: ANALISIS NARATIF MULTI-PLATFORM - Yusril Ihza Saputra; Hafidatun Nabila; Aminullah Aminullah; Uryatul Hikmah; Moh. Holidi; Abu Hasan Agus R (Jurnal Manajemen Pendidikan, 2026)
Technological advancements are driving educational institutions to build their image and competitiveness through digital branding strategies. This study aims to evaluate the digital branding strategy at MA Manbaul Ulum Tangsil Wetan Bondowoso, particularly from the audience’s perspective regarding the implementation of such branding. This study employs a qualitative method using a case study approach and grounded theory. Research data were collected through interviews, observations, and desk reviews from informants such as students, parents, and institutional administrators. Data was analyzed through the stages of data condensation, data reduction, data presentation, and verification. The results indicate that although the organization utilizes digital platforms to disseminate academic information and religious activities, there is a lack of audience engagement and depth in the religious content presented. The audience felt that digital branding emphasized academic information more and placed less emphasis on religious values as the institution’s identity. These findings underscore the importance of Islamic educational institutions balancing the delivery of academic information and religious value-based content, as well as enhancing audience engagement through digital communication to strengthen relationships with the audience.